Unit reliability and integrity process development and implementation. Issue 2 (13th November 2018) - Hanning, David
Abstract : A little over 10 years ago, Chevron developed and implemented an Asset Reliability Process with the goal of improving the reliability of our facilities, with a strong focus on improving the availability of our facilities. This was known as URIP or our Unit Reliability Improvement Process. The building blocks of this process include subprocedures for: Design for reliability Reliability opportunity identification and resolution Risk assessment and asset strategy Surveillance and condition monitoring Proactive maintenance Maintenance and failure prevention While we were successful in improving the availability of our facilities with the implementation of URIP, we continued to experience incidents and unplanned downtime associated with the integrity of our assets. As a result, we identified the need to revise our process to place a greater focus on asset integrity. This presentation describes the development and implementation of our revised reliability process, which we have renamed as our Unit Reliability and Integrity Process. The resulting asset care program still includes the subprocedures listed above, with the incorporation of asset integrity requirements. © 2018 American Institute of Chemical Engineers Process Saf Prog 38: e12018, 2019